A Case Study: Ayurvedic Management of Nasarsha w.s.r to Nasal Polyp - Ramya , M; Rathi, S (International Research Journal of Ayurveda & Yoga, 2023)
Nasa is the most important organ of Urdhwajatrugatabhaga and is the gateway for head as well as respiratory system. Nasarshas is one among the thirty-one Nasagata Rogas mentioned in our classics. Nasarshas can be correlated to nasal polyps. Nasal polyps are non-neoplastic masses of nasal or sinus mucosa. Prolonged use of antihistamines and antibiotics leads to drug resistance and decreases immunity, Fear of surgery, its complications and cost have restricted many patients from undergoing surgery and allopathic medicines. In this study a case of 31years male Patient presented with difficulty in nasal breathing, mouth breathing especially at night, sneezing, nasal discharge, headache since 9 months was taken for study. Present case study is taken to evaluate the efficacy of Ksharakarma in the management of Nasarshas w.s.r to Nasal Polyp along with internal medications for improve immunity and to reduce its recurrence. Kshara is an excellent medicine in the management of Arsha, as it has Lekhana, Tridoshaghna, Teekshna and Ushna properties. Shirovirechana being one of the Shodhana Karma, hence Nasya with Apamarga Kshara Taila followed by Yava kshara prathisarana was planned. Internally, Chitrakadi Vati, Triphala Guggulu and Haridra khanda, Hamsapadi Kashaya was prescribed. There was significant improvement in patient’s complaints and marked reduction in polypoidal mass.